The living State and education for peace - Rivera Alfaro, Ronald (2026)
This article reflects on the concept of the State as a living entity and its relation to the construction of a culture of peace in Latin America, particularly in Costa Rica. It is contextualized within the socio-pedagogical project “Socio-pedagogical Plan for the Implementation of a Culture of Peace in Santa Bárbara de Heredia,” developed at the Universidad Nacional. The methodology is based on documentary analysis and theoretical reflection derived from academic conferences and debates aimed at understanding citizen security as a political and social phenomenon. The main findings show that globalization processes, market transnationalization, and weakened state sovereignty have conditioned governance and have limited the capacity of the State to address crime, guarantee rights, and promote peace. The analysis also examines how Latin American history has shaped political cooperation blocks which, although fragile, have created spaces for dialogue around social justice and education. It is concluded that peace education is a key tool to strengthen citizen participation, promote critical thinking, and establish sustainable development based on human rights and social justice.